Sounding the Sacred: Qur'anic Soundscapes in Javanese Muslim Traditions - Alam, Lukis; Masudi, Muhammad Maulana; Munawar, Said Agil Husin Al; Sidqi, Hisam (Universitas Muhammadiyah Surakarta, 2025)
This study examines how sound and community are essential for understanding the Qur'an in Javanese Muslim settings, where recitation is essential. It investigates how Qur'anic soundscapes serve as a form of contextual tafsīr during communal rituals. The research was conducted in Yogyakarta, Kudus, and Surabaya from February to June 2025. This study employs participant observation and informal interviews to examine Qur'anic recitation within communal gatherings, including pengajian wetonan, tahlilan, and slametan. The findings show that sound serves as an embodied hermeneutics, influenced by emotional resonance and Javanese values such as rukun (harmony) and unggah-ungguh (respect). Kyais and pesantren communities are key in mediating these interpretations. This work contributes to contextual Qur'anic studies by framing listening as a mode of exegesis that encompasses sonic, affective, and communal dimensions of Javanese Islam.